Public and private just wars: Distributed cyber deterrence based on Vitoria and Grotius - Johannes Thumfart (Internet Policy Review, 2020)
This contribution discusses the growing importance of cyber attacks directed at the public sphere and the crucial role of non-state actors in cyber attacks from a perspective of just war theory. Going back to Grotius’ and Vitoria’s seminal teachings on international law, the article makes the case for distributed cyber deterrence involving private and public actors. Further, it justifies sanctions for cyber attacks that do not cause physical violence, for example the interference with elections or the hacking of companies. It considers the post-physicality of cyberspace, the attribution problem, private just war theory and national self-determination through deliberation.